Activity size distribution of radioactive nuclide 7Be at different locations and under different meteorological conditions - Ioannidou, A.; Groppi, F.; Bonardi, M. L.; Manenti, S.; Gini, L. (HNPS Advances in Nuclear Physics, 2019)
The activity size distributions of the natural radionuclide tracer 7Be in different size fractions (<0.4 μm, 0.4-0.7 μm, 0.7-1.1 μm, 1.1-2.1 μm, 2.1-3.1 μm, 3.1-4.2 μm, 4.2-5.8 μm, 5.8-9.0 μm >9.0 μm) were determined at different site places in Northern Italy. Samplings were carried out during the four different seasons of the year 2011. The aim of this work was to define any differences due to the different environments and different meteorological conditions and clarify the main parameters influencing the activity size distribution of radioactive aerosols.